Brazilian political system - Marcos Augusto Maliska (KSU Publ., 2014)
The article deals with the subjects of the political system of Brazil, particularly their legal status in the government. Particular attention is given to the characteristic features of the legislative, executive and judicial branches of power, and their competence. The author reveals some features of the system of regulations adopted by government entities.
Бразилияның саяси жүйесі
Бразильская политическая система
Keywords: Political system; president; Parliamentary immunity; national congress